Kontribusi Media Internet Dan Intensitas Belajar TerhadapOptimalisasi Keaktifan Belajar Teori Akuntansi PadaMahasiswa Pendidikan Akuntansi FKIP UniversitasMuhammadiyah Surakarta Tahun Ajaran 2015/2016 - Yusuf, Nur Muhammad, Dr.Suyatmini,SE.,M.Si (2016)
The objectives of this research are to know: the contribution 1) internet media toward the optimalization of learning activeness of accounting theory at Department of Accounting Education's students, School of Teacher Training and Education, Muhammadiyah University of Surakarta 2015/2016 academic year. 2) learning intensity toward the optimalization of learning activeness of accounting theory at Department of Accounting Education's students, FKIP Muhammadiyah University of Surakarta 2015/2016 academic year. 3) internet media and learning intensity toward the optimalization of learning activeness of accounting theory at Department of Accounting Education's students FKIP Muhammadiyah University of Surakarta 2015/2016 academic year. This research employs quantitative associative method. The population in this research is the Department of Accounting Education's students FKIP Muhammadiyah University of Surakarta 2015/2016 academic year which consist of 100 students. The sampling technique used in this research is Proportional Random Sampling as many as 78 respondents. The data needed are acquired through documentation and questionnaire which have been tested with validity and reability test. The data analysis technique used in this research is double regression linear test, t test, F test, R2 test and relative and effective contribution. The result of regression test are acquired regression equation: Y= 1,959 + 0,452X1 + 0,494X2. The conclusion of this research are: 1) Internet media has significant contribution toward the optimalization of learning activeness. Based on t test are acquired thitung> ttabel that is 3,565 > 1,992 (α=5%) and significancy score < 0,05 that is 0,000. 2) Learning intensity has significant contribution toward the optimalization of learning activeness. Based on t test are acquired thitung> ttabel that is 4,480 > 1,992 (α=5%) and significancy score < 0,05 that is 0,000. 3) Internet media and learning intensity has significant contribution toward the optimalization of learning activeness. Based on F test are acquired Fhitung> Ftabel that is 112,581 > 3,119 on significant rate 5%. 4) X1 variable gives relative contribution as much as 44,53% and effective contribution as much as 33,4%, X2 variable gives relative contribution as much as 55,47% and effective contribution as much as 41,6%. 5) the result of R2 acquired 0,750, means 75,0% the optimalization of learning activeness of accounting theory is affected by internet media and learning intensity, 25% remaining is affected by other variable outside of the research.